The magnitude of pediatric mortality and determinant factors in intensive care units in a low-resource country, Ethiopia: a systematic review and meta-analysis - Molla, Misganew Terefe; Endeshaw, Amanuel Sisay; Kumie, Fantahun Tarekegn; Lakew, Tigist Jegnaw (Frontiers in Medicine, 2023)
Background Pediatric mortality after being admitted to a pediatric intensive care unit in Ethiopia is high when compared to high-income countries. There are limited studies regarding pediatric mortality in Ethiopia. This systematic review and meta-analysis aimed to assess the magnitude and predictors of pediatric mortality after being admitted to an intensive care unit in Ethiopia. Methods This review was conducted in Ethiopia after retrieving peer-reviewed articles and evaluating their quality using AMSTAR 2 criteria. An electronic database was used as a source of information, including PubMed, Google Scholar, and Africa Journal of Online Databases, using AND/OR Boolean operators. Random effects of the meta-analysis were used to show the pooled mortality of pediatric patients and its predictors. A funnel plot was used to assess the publication bias, and heterogeneity was also checked. The final result were expressed as an overall pooled percentage and odds ratio with a 95% confidence interval (CI) of < 0.05%. Results In our review, eight studies were used for the final analysis with a total population of 2,345. The overall pooled mortality of pediatric patients after being admitted to the pediatric intensive care unit was 28.5% (95% CI: 19.06, 37.98). The pooled mortality determinant factors were included the use of a mechanical ventilator with an odds ratio (OR) of 2.64 (95% CI: 1.99, 3.30); the level of Glasgow Coma Scale <8 with an OR of 2.29 (95% CI: 1.38, 3.19); the presence of comorbidity with an OR of 2.18 (95% CI: 1.41, 2.95); and the use of inotropes with an OR of 2.36 (95% CI: 1.65, 3.06). Conclusion In our review, the overall pooled mortality of pediatric patients after being admitted to the intensive care unit was high. Particular caution should be taken in patients on the use of mechanical ventilators, the level of Glasgow Coma Scale of <8, the presence of comorbidity, and the use of inotropes. Systematic review registration https://www.researchregistry.com/browse-the-registry#registryofsystematicreviewsmeta-analyses/, identifier: 1460.